Quantifying melt production and degassing rate at mid‐ocean ridges from global mantle convection models with plate motion history. (31st July 2016) - Li, Mingming; Black, Benjamin; Zhong, Shijie; Manga, Michael; Rudolph, Maxwell L.; Olson, Peter
Abstract: The Earth's surface volcanism exerts first‐order controls on the composition of the atmosphere and the climate. On Earth, the majority of surface volcanism occurs at mid‐ocean ridges. In this study, based on the dependence of melt fraction on temperature, pressure, and composition, we compute melt production and degassing rate at mid‐ocean ridges from three‐dimensional global mantle convection models with plate motion history as the surface velocity boundary condition. By incorporating melting in global mantle convection models, we connect deep mantle convection to surface volcanism, with deep and shallow mantle processes internally consistent. We compare two methods to compute melt production: a tracer method and an Eulerian method. Our results show that melt production at mid‐ocean ridges is mainly controlled by surface plate motion history, and that changes in plate tectonic motion, including plate reorganizations, may lead to significant deviation of melt production from the expected scaling with seafloor production rate. We also find a good correlation between melt production and degassing rate beneath mid‐ocean ridges. The calculated global melt production and CO2 degassing rate at mid‐ocean ridges varies by as much as a factor of 3 over the past 200 Myr. We show that mid‐ocean ridge melt production and degassing rate would be much larger in the Cretaceous, and reached maximum values at ∼150–120 Ma. Our results raise the possibility that warmer climate in the Cretaceous could be due in part to high magmatic productivity and correspondingly high outgassing rates at mid‐ocean ridges during that time. Key Points: We develop tools to quantify melt flux and degassing rate in mantle convection models Mid‐ocean ridge melt production is mainly controlled by plate motion history Ridge jump causes deviation of melt flux from that scaled by seafloor production rate